2015
DOI: 10.2752/089279315x14219211661732
|View full text |Cite
|
Sign up to set email alerts
|

Local Insects as Flagship Species to Promote Nature Conservation? A Survey among Primary School Children on Their Attitudes toward Invertebrates

Abstract: Flagship species play an important role in promoting nature conservation. However, although the significance of invertebrates in biodiversity and ecosystem services is undisputed, they are rarely used as flagship species. A focused approach to better understand the drivers of differences in attitudes toward invertebrates, and insects in particular, would be helpful for selecting and establishing insects as flagship species, especially in a local context for local conservation purposes. Using a standard questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Our study found that people show more positive attitudes toward conservation of bees than we would have expected. Besides being quite popular, bees also meet all criteria to be selected as flagship species as described by Schlegel et al[ 70 ]: According to their criteria, bees (i) are local species in most parts of the world [ 71 ], (ii) are ecological key players because of their pollinating service [ 2 ], (iii) should be identified for example because of their prominence in most educational curricula and current media, (iv) but are not explicitly used as flagship species yet, (v) have a familiar name which is known across all ages and levels of expertise. Consequently, we strongly propose using bees, for instance Apis mellifera , as a flagship species for local conservation of pollinating insects.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that people show more positive attitudes toward conservation of bees than we would have expected. Besides being quite popular, bees also meet all criteria to be selected as flagship species as described by Schlegel et al[ 70 ]: According to their criteria, bees (i) are local species in most parts of the world [ 71 ], (ii) are ecological key players because of their pollinating service [ 2 ], (iii) should be identified for example because of their prominence in most educational curricula and current media, (iv) but are not explicitly used as flagship species yet, (v) have a familiar name which is known across all ages and levels of expertise. Consequently, we strongly propose using bees, for instance Apis mellifera , as a flagship species for local conservation of pollinating insects.…”
Section: Discussionmentioning
confidence: 99%
“…For non-parasitic invertebrates, public perceptions are largely dependent on experience and familiarity (Schlegel et al, 2015;Schlegel and Rupf, 2010), and one well-known method for familiarizing people with biodiversity is to engage them with anthropomorphized cartoons (Chan, 2012;Tam et al, 2013). This approach is already being used to some degree for parasites.…”
Section: Goal 11 Raise Awareness For Parasite Conservation Through Media and Public Educational Venuesmentioning
confidence: 99%